Shared but Threatened: The Heritage of Wild Food Plant Gathering among Different Linguistic and Religious Groups in the Ishkoman and Yasin Valleys, North Pakistan - Muhammad Abdul Aziz (Foods, 2020)
A wild food ethnobotanical field study was conducted in the Ishkoman and Yasin valleys, located in the Hindukush Mountain Range of Gilgit-Baltistan, northern Pakistan. These valleys are inhabited by diverse, often marginalized, linguistic and religious groups. The field survey was conducted via one hundred and eighty semistructured interviews to record data in nine villages. Forty gathered wild food botanical and mycological taxa were recorded and identified. Comparative analysis among the different linguistic and religious groups revealed that the gathered wild food plants were homogenously used. This may be attributed to the sociocultural context of the study area, where most of the population professes the Ismaili Shia Islamic faith, and to the historical stratifications of different populations along the centuries, which may have determined complex adaptation processes and exchange of possibly distinct pre-existing food customs. A few wild plants had very rarely or never been previously reported as food resources in Pakistan, including Artemisia annua, Hedysarum falconeri, Iris hookeriana, Lepidium didymium and Saussurea lappa. Additionally, the recorded local knowledge is under threat and we analyzed possible factors that have caused this change. The recorded biocultural heritage could, however, represent a crucial driver, if properly revitalized, for assuring the food security of the local communities and also for further developing ecotourism and associated sustainable gastronomic initiatives in the area.